Association of the Duration of Active Pushing With Obstetric Outcomes - William A. Grobman; Jennifer L. Bailit; Yinglei Lai; Uma M. Reddy; Ronald J. Wapner; Michael W. Varner; Steve N. Caritis; Mona Prasad; Alan Tita; George R. Saade; Yoram Sorokin; Dwight J. Rouse; et al. (2016)
In Brief OBJECTIVE: To estimate the associations between the duration of active pushing during the second stage of labor and maternal and neonatal outcomes. METHODS: We performed an observational study in which data were obtained by trained abstractors from maternal and neonatal charts of deliveries at 25 hospitals over a 3-year period. In this secondary analysis, women with no prior cesarean delivery who had a term, singleton, cephalic gestation and reached complete dilation were analyzed. The duration of pushing, defined as the time from initiation of pushing to either vaginal delivery or the decision to proceed with a cesarean delivery, was determined. The primary maternal outcome was cesarean delivery and the primary neonatal outcome was a composite that included: mechanical ventilation, proven sepsis, brachial plexus palsy, clavicular fracture, skull fracture, other fracture, seizures, hypoxic–ischemic encephalopathy, or death. Nulliparous and parous women were analyzed separately in univariable and then multivariable analyses. RESULTS: A total of 53,285 women were analyzed. In both nulliparous and parous women, longer duration of pushing was associated with increased odds of both cesarean delivery and the neonatal adverse outcome composite. Nevertheless, even after 4 hours of pushing, approximately 78% of nulliparous women who continued with active pushing had a vaginal delivery and more than 97% did not have the composite adverse neonatal outcome. Similarly, after more than 2 hours of pushing, approximately 82% of parous women who continued active pushing delivered vaginally and more than 97% did not have the adverse neonatal outcome. CONCLUSION: A longer duration of pushing is associated with an increased relative risk, but small absolute difference in risk, of neonatal complications. Approximately 78% of nulliparous women delivered vaginally even after 4 hours of pushing. A longer duration of pushing is associated with an increased relative risk, but a small absolute difference in risk, of neonatal complications.